Pengaruh Model Pembelajaran Berbasis Masalah dan Sikap pada Fisika Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik - Sadiah, Riskha Lestari; Ali, Muh. Sidin; Khaeruddin, Khaeruddin; Helmi, Helmi; Arsyad, Muh. (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
This study aims to analyze the effect of learning models and attitude in physics on the problem solving. This research is a true experiment with a 2x2 factorial design. The population is all class X SMA Negeri 7 Luwu Utara years 2022/2023. The sample of two classes using simple random sampling techniques. Methods of data collection using attitude questionnaire on physics and physics problem-solving skill tests. Data analysis using two-way ANOVA The results showed that: There were differences in the physics problem-solving skills of students who were taught using problem-based learning models and those who were taught using discovery learning models, for attitudes to high physics, there were differences in problem-solving skills physics taught using problem-based learning models with those taught using discovery learning models, for low physics attitudes, there are differences in the physics problem-solving skills of students who are taught using problem-based learning models with those taught using discovery learning models, and there is no interaction between the learning model and attitudes toward physics on students' physics problem-solving skills. Keywords: PBL, attitude in physics, problem solving skill.